Daya Penyebaran dan Derajat Kepekaan Sektor Pertanian dalam Pembangunan Ekonomi di Provinsi Jawa Tengah - Imas Wildan Rafiqah; Darsono Darsono; Joko Sutrisno (AGRARIS: Journal of Agribusiness and Rural Development Research, 2018)
This research aimed to analyze the power of dispersion and sensitivity of dispersion of the agricultural sector on the economic development of Central Java Province. This research used the data of Input and Output Table of Central Java in 2013. Data analysis method applied in this research is Input-Output analysis. The results showed that the agricultural sector represented by the livestock sector had ‘above average’ power of dispersion index of the overall index. Livestock sector was able to encourage the production growth in all sectors of the economy. On the other hand, the sensitivity of dispersion index of all agricultural sectors was lower than the average value of the overall index. This reflects the agricultural sector’s low sensitivity to the changes of the external aspects which results in the low forward linkage among the downstream sectors. In term of key sector identification, the agricultural sector as a whole was not classified in the priority sector I. However, the livestock subsector, representing the agricultural sector, was classified in the priority sector II on the economic development of Central Java Province.